International Trade and World Goods Markets: The textbook - Khussainova, Zh.S.; Zhartay, Zh.M.; Gazizova, M.R. (Tengri, 2016)
The textbook contains the systematized information about the exchange of capital, goods, and services across international borders or territories, which could involve the activities of the government and individual. International trade is also a branch of economics, which, together with international finance, forms the larger branch called international economics. The textbook is addressed to students, masters of economic specialties and teachers, and also it can be useful for all who is interested in problems of international trade and world goods markets.
Keywords: International Trade; World Goods Markets